Pengaruh Kebijakan Dana Desa dan Pembangunan Ekonomi Terhadap Infrastruktur Perdesaan di Desa Ria Raja Kecamatan Ende - Gaut , Ermelinda Inus; Leha, Ernesta; Paulus Luciany, Yohanes (Program Studi Ekonomi Pembangunan Universitas Flores, 2022)
This study aims (1) to determine the effect of the Fund Policy Villages Againts Rural Infrastructure in Ria Raja Village, Ende Distric (2) To understand the direction of economic development towards rural infrastructure in Ria Raja Village, Ende sub-distric. This research is descriptive quantitative research, because this research aims to get an overview, describe, describe and report a kradan, object or event to describe village fund policies and development. Economics on rural infrastructure in Ria Raja Village. The sampel in this study was the people of Ria Raja Village, which amounted to 40 gangs. Data were collected using a questionnaire that had been tested for validity and reliability, with multiple linear regression analysis techiniques used to test the research hypotheses. This This results of this study indace that (1) the village fund policy partially and significantly influences rural infrastructure in Ria Raja Village, Ende Distric. This can be seen from the valule of the things of 6,916 and the bell of 1,687(df-n-k-1) with a significance level of 0,000, because the table is (6,916> 1,687), the significance is smaller than 0,05 (0,000 < 0,05). (2) Economic development partially and significantly affects rural infrastructure in Ria Raja Village, Ende Distric. This can be seen from the size of the Temas value of 2,468 and the tabal value of 1,687 (df-n-k-1) with a significance level of 0,021, because titling > toll (2,648 > 1,687), the signiicance is smaller than 0,05 (0,021 < 0,05).